2014
DOI: 10.4274/turkderm.82957
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-23 levels in patients with vitiligo

Abstract: Background and Design: Interleukin-23 (IL-23) is a cytokine which is believed to have an important role in the pathogenesis of autoimmune diseases. Therefore, it can be used as a target molecule in the treatment of autoimmune diseases. The aim of our study was to determine serum IL-23 levels in patients with vitiligo to understand their possible roles in the disease etiology and to compare the results with the healthy controls. Materials and Methods: Fifty-one patients, who applied to the dermatology outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Another study identified lower serum IL‐23 levels in vitiligo patients compared to control, although this was not statistically significant. Both studies did not control for vitiligo type 61,62 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study identified lower serum IL‐23 levels in vitiligo patients compared to control, although this was not statistically significant. Both studies did not control for vitiligo type 61,62 …”
Section: Resultsmentioning
confidence: 99%
“…Both studies did not control for vitiligo type. 61,62 There have been several cases of successful treatment of vitiligo with IL-23 inhibitors. A total of six studies involved IL-23 inhibitors.…”
Section: Interleukin-23 Biologicsmentioning
confidence: 99%
“…Although the definite cause of the ailment has not yet been determined, a number of theories linking it with autoimmune, cytotoxic, biochemical, neural, and oxidant-antioxidant mechanisms have been proposed. The role of viruses and genetics has also been looked into while studying the disease [ 1 , 2 ]. Vitiligo patients display increased oxidative stress in blood as well as epidermis [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%